Distribution of Neuroendocrine Cells in the Transition Zone of the Prostate - Yuki Kyoda; Koji Ichihara; Kohei Hashimoto; Ko Kobayashi; Fumimasa Fukuta; Naoya Masumori (Advances in Urology)
Objectives. To evaluate the distribution of neuroendocrine (NE) cells which may influence the development of benign prostatic hyperplasia (BPH) in the transition zone (TZ). Methods. We reviewed specimens from 80 patients who underwent radical prostatectomy in our institution and evaluated the density of NE cells in the TZ. They were histologically classified into 3 groups: those with no adenomatous nodule in the TZ (group A), those with small nodules with normal epithelium and stroma around them in the TZ (group B), and those with large nodules occupying the TZ (group C). In the patients of group B, intra-adenoma (adenomatous nodules) and extra-adenoma (normal tissue) NE cells in the TZ were separately counted. Results. There were 22, 23, and 35 patients in groups A, B, and C, respectively. The median density of NE cells in the TZ of group B patients, 2.80/mm2, was significantly higher than that of NE cells in group A, 1.43/mm2, and group C, 0.61/mm2 (p<0.001). In group B, the median density of extra-adenoma NE cells was significantly higher than that of intra-adenoma. Conclusions. Many NE cells exist around small adenoma in the TZ. NE cells may influence the initial growth of BPH in a paracrine fashion. Trial Registration. This study approved by our institutional review board was retrospectively registered (#272-14).